The Effect Of Self-Regulation And Wages On Work Motivation With Psychological Well-Being As A Mediator Variable In Indonesian Construction Interns In Saitama, Japan - Dorothea Diana Feliarosa; Dewi Yustiana; Immanuel Ustradu Osijo; Sutoyo; Sutomo (Abadi Institute, 2026)
This study aims to analyze the influence of self-regulation and wages on work motivation with psychological well-being (PWB) as a mediator variable in Indonesian construction interns in Saitama, Japan. The background is based on the adaptation challenges and work pressures faced by migrant workers, while higher wages are the main attraction. This study examines whether self-regulation and financial compensation can improve work motivation, either directly or through improved psychological well-being. The research uses an explanatory quantitative approach with a survey method. Data were collected through questionnaires from 205 respondents selected by purposive sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) with Partial Least Square (PLS) through SmartPLS 4.0 software to test the direct and indirect relationships between variables. The results of the study show that all hypotheses are accepted. Self-regulation and wages have a positive and significant effect on psychological well-being (H1 & H2) as well as on direct work motivation (H3 & H4). Psychological well-being has also been shown to have a significant positive effect on work motivation (H5). Furthermore, psychological well-being acts as a partial mediator in the indirect relationship between self-regulation (H6) and wages (H7) to work motivation. This means that increased self-regulation and wages not only directly boost work motivation, but also significantly strengthen it through improved psychological well-being. In conclusion, the work motivation of Indonesian construction interns in Japan can be improved by developing self-regulation skills, establishing a decent and fair wage system, and specifically prioritizing programs that support their psychological well-being. This research contributes to the development of cross-cultural human resource management theory and practical implications for intern companies and program organizers.